The logical relations of opposition and how to teach them - López-Astorga, Miguel (Opción, 2016)
Based on the mental models theory, in this paper, I try to identify which of the relations of opposition in Aristotelian logic can be often difficult to understand for the students. In this way, assuming the distinction that the theory proposes between canonical and noncanonical models, I analyze all of the relations of opposition in order to detect which of them require to manipulate canonical models and, therefore, more cognitive effort. In addition, I comment on the kinds of sentences that should be used as examples to make the learning process of the problematic relations easier.